Anterior transpedicular screw fixation of cervical spine: Is it safe? Morphological feasibility, technical properties, and accuracy of manual insertion - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2015)
OBJECT Due to lack of construct stability of the current anterior cervical approaches, supplemental posterior cervical approaches are frequently employed. The use of an anterior-only approach with anterior transpedicular screws (ATPSs) has been proposed as a means of providing 3-column fixation. This study was designed to investigate the feasibility of anterior transpedicular screw (ATPS) fixation of cervical spine, to obtain the morphological measurements for technical prerequisites, and to evaluate the accuracy of the ATPS using fluoroscopy. METHODS The study included both radiological and anatomical investigations. The radiological investigations were based on data from cervical spine CT scans performed in 65 patients. Technical prerequisites of ATPS were calculated using OsiriX for Mac OS. In the anatomical part of the study, 30 pedicles (C3-7) from 6 formalin-preserved cadavers were manually instrumented. Measurements obtained included pedicle width (PW), pedicle height (PH), pedicle transverse angle (PTA), distance of the entry point from the midline (DEPM), and distance of the entry point from the superior endplate (DEPSEP). The authors also analyzed screw position in the manually instrumented vertebrae. RESULTS The mean PW and PH values showed a tendency to increase from C-3 to C-7 in both males and females. The means were significantly larger for both PW and PH in males than in females at all levels (p = 0.001). The overall mean PTA value was significantly lower at C-7 (p < 0.0001). The mean value for the distance of entry point from the midline (DEPM) represented a point at the contralateral side of the pedicle for every level except C-7. The mean DEPSEP values showed significant differences between all levels (p < 0.0001). Seven of the 30 screws were identified as breaching the pedicle (23.3%); these screw malplacements were seen at C-3 (3 screws), C-4 (2 screws), and C-5 (2 screws). CONCLUSIONS The morphological measurements of this study demonstrated that ATPS fixation is feasible in selected cases. They indicate that ATPS insertion using a fluoroscopy-assisted pedicle axis view is safe at the C-6 and C-7 levels, but the results at the other levels did not prove the safety of this technique.
Keywords: anterior transpedicular screw fixation; fluoroscopy; accuracy; cervical; pedicle; anatomy; PEDICLE SCREW; COMPUTED-TOMOGRAPHY; PLACEMENT; RECONSTRUCTION; COMPLICATIONS; DIMENSIONS; CORPECTOMY; STRENGTH; 4-LEVEL; MIDDLE